Kebugaran Jasmani Personel Brimob Kota Surakarta Berdasarkan Tes Fisik Kesamaptaan A Lari 12 Menit - Mukhsin Abdurrahman; Gatot Jariono; Nurhidayat Nurhidayat; Akhmad Azlan Khoirur Rozikin; Ardhian Tomy Kurniawan (Jurnal Porkes, 2026)
The physical fitness of Mobile Brigade Corps (Brimob) personnel is a crucial factor supporting operational readiness in carrying out demanding tasks such as counterterrorism and crowd control. However, the physical fitness level of young Brimob personnel at the Headquarters of Battalion C Pelopor of the Central Java Regional Police, as measured by the 12-minute run fitness test standard A, has not yet been empirically determined. This study aims to analyze the physical fitness levels of these personnel. The method used is quantitative descriptive analysis employing a survey technique via the 12-minute run test. The sample consisted of 20 male adolescent personnel selected through purposive sampling. Data were analyzed using descriptive statistics (mean, standard deviation, and frequency percentages). The results showed an average distance covered of 2,662 meters, with a maximum of 2,970 meters and a minimum of 2,350 meters. A total of 70% of the personnel fell into the “Good” category, 25% into the “Very Good” category, and only 5% into the ‘Fair’ category. In conclusion, the physical fitness level of the Brimob youth personnel is classified as good; however, there are still variations in ability that require individualized training programs and routine evaluations to improve personnel performance toward the “Excellent” category.